GAS REMOVAL SYSTEM OPTIMIZATION IN KAMOJANG UNIT 2 GEOTHERMAL POWER PLANT - KRISNA DANA PUTRA (NIM : 131 06 097); Pembimbing : Prof. Dr. Ir. T.A. Fauzi Soelaiman, MSME, ARIEF
Kamojang Unit 2 Geothermal Power Plant is one of the geothermal power plants owned by PT. Indonesia Power with a capacity of 55 MW. As the gas removal system (GRS) it uses ejector two levels. Steam consumption required for the GRS is the reason to optimize on the GRS. The study starts by varying the configuration of GRS into two level ejector GRS, two level of hybrid GRS, three level ejector GRS, three level of hybrid GRS (2 ejector and 1 LRVP), three level of hybrid (1 ejector and 2 LRVP), two level LRVP GRS, and one level ejector GRS. The most optimal method is determined from the minimum of the required motive steam and the large savings. A model is developed using Microsoft Macro Excel VBA (Visual Basic Analysis) and is intended to determine the overall condition of power plant performed during the optimization. To ensure a level of confidence of the modeling results, validation was performed against the design conditions. Optimization was performed is based on the intercondenser and aftercondenser pressures. The optimization shows that minimum motive steam can be obtain by using two level LRVP GRS, which is 1311 kg/hr. After conversion to the price of steam and electric power prices, the largest saving can be obtained by the two level LRVP GRS, which is equal to 6.9 billions of rupiah per year. Based on the calculation, the two level LRVP GRS is the most appropriate for the GRS on Kamojang Unit 2 Geothermal Power Plant.